Modified Random Sequential Adsorption Model for Understanding Kinetics of Proteins Adsorption at a Liquid-Solid Interface - Min, Hwall (Langmuir : the ACS journal of surfaces and colloids, 2017)
In this Article, we experimentally measure the adsorption kinetics of human serum albumin (HSA) on a hydrophobic hexadecanethiolated gold surface. We use micromachined quartz crystal resonators with fundamental frequency of 83 MHz to accomplish these measurements in real time. In this work, we focus on two key results: (i) asymptotic behavior of the sensor responses upon HSA adsorption and (ii) the jamming limit of adsorbed layer formed by both single-injection and multi-injection experiments with the same value of final concentration. We develop a new interface-depletion modified random sequential adsorption (RSA) model to elucidate the adsorption kinetics and the transport properties of the protein molecules. Analysis of the experimentally measured data shows that the results can be explained on the basis of the exponentially depleting interfacial layer RSA model. To better understand the origin of the formation of the interfacial depletion region where the supply of protein molecules is dramatically reduced, we performed a series of molecular dynamics (MD) simulations using the ReaxFF method. These simulations predict that the resulting adsorption of the protein molecules on the thiolated surface results in a specific orientation at the interface and the diffusion constant of the protein molecules in this layer is significantly reduced. This interplay between the surface adsorption rate and the reduced diffusion coefficient leads to the depletion of the protein molecules in the interfacial layer where the concentration of the protein molecules is much less than the bulk concentration and explains the observed slowdown of the HSA adsorption characteristics on a hydrophobic surface